IMPLEMENTATION OF THE TAKROR METHOD DALAM MENINGKATKAN PEMAHAMAN MATA PELAJARAN SHORROF DI PONDOK PESANTREN DARUMAFATIHIL ULUM PODOKATON BAYEMAN GONDANGWETAN PASURUAN - Sofiyulloh (Center of Education Journal (CEJou), 2023)
Learning methods in educational institutions are very effective in the learning process so they can provide the best learning results. So that education observers compete to create an education system in such a way that they look at the field problems that occur. One of them is using the takror method or repeating material that has been taught by the teacher by presenting it in front of other students as explained by the teacher to the students. The aims of this research are 1) To describe the implementation of the takror method at the Darumafatihil Ulum Podokaton Bayeman Gondangwetan Pasuruan Islamic Boarding School, 2) To find out the factors that support the level of understanding of students in shorrof subjects at the Darumafatihil Ulum Podokaton Bayeman Gondangwetan Pasuruan Islamic Boarding School and 3) To find out the implications takror method in increasing understanding of shorrof subjects at the Darumatihil Ulum Podokaton Bayeman Gondangwetan Pasuruan Islamic Boarding School. This research uses a qualitative research approach. Meanwhile, the type of research used by researchers is descriptive. The primary data sources in this research are the caregivers, teachers, administrators and students of the Darumafatihil Ulum Podokaton Bayeman Gondangwetan Pasuruan Islamic Boarding School. Data collection techniques are direct observation, structured interviews and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. Checking data wetness using triangulation. The results of the research show that 1) The implementation of the takror method at the Darumafatihil Ulum Podokaton Bayeman Gondangwetan Pasuruan Islamic Boarding School is carried out in two stages, namely the preparation stage: a) The takror administrators and students are present before 20.00 b) The students read nadoman or memorize tasrifan shorrof c) The takror administrators prepare supporting facilities. Implementation stage: a) Takror activities are held from 20.00-21.30, b) Students repeat learning material, c) Takror administrators explain material that is not yet understood. 2) Factors that support the level of understanding of students in shorrof subjects at the Darumafatihil Ulum Podokaton Bayeman Gondangwetan Pasuruan Islamic Boarding School are influenced by several very important factors, including: a) The quality of accompanying teachers, b) The students' high learning motivation, c) The existence of support from people old. 3) There are two implications of the takror method in increasing understanding of shorrof subjects at the Darumafatihil Ulum Podokaton Bayeman Gondangwetan Pasuruan Islamic Boarding School, namely: 1) Implications for students 2) Implications for institutions.